METTL3-mediated m6A modification enhances ZDHHC16 expression in nonsmall- cell lung cancer patients, attenuating ferroptosis by suppressing CREB ubiquitination: METTL3 upregulation reduces ferroptosis in lung cancer - Liu, Zeyu; Jing, Chuanqing; Zhang, Wei (Cellular and Molecular Biology, 2024)
At present, the early diagnosis and treatment of non-small cell lung cancer (NSCLC) is still an urgent problem to be solved worldwide, including in China. The present work investigated the possible protective effect of ZDHHC16 in cell proliferation and metastasis of NSCLC and explored its possible mechanisms. ZDHHC16 expression level in patients with Non-Small-Cell Lung Cancer was up-regulation. ZDHHC16 gene is stabilized by m6A methylation. ZDHHC16 gene reduced ferroptosis of NSCLC by the rehabilitation of the mitochondrial structure. ZDHHC16 promoted CREB expression through the inhibition of CREB Ubiquitination. Confocal microscopy showed that ZDHHC16 reduced the CREB expression of NSCLC. ZDHHC16 up-regulation reduced CREB Ubiquitination, and down-regulation of ZDHHC16 promoted CREB Ubiquitination of NSCLC. CREB Agonists reduced the effects of ZDHHC16 on ferroptosis, not affecting the Warburg effect of NSCLC. CREB inhibitor reduced the effects of si-ZDHHC16 on ferroptosis, not affecting the Warburg effect of NSCLC. METTL3-mediated m6A modification increases ZDHHC16 stability. Our study revealed that the m6A-forming enzyme METTL3 upregulates ZDHHC16 expression in NSCLC patients, leading to the reduction of ferroptosis by inhibiting CREB ubiquitination.